The phytoremediation of an organic and inorganic polluted soil: A real scale experience. Issue 4 (2nd April 2016) - Macci, C.; Peruzzi, E.; Doni, S.; Poggio, G.; Masciandaro, G.
ABSTRACT: A phytoremediation process with horse manure, plants ( Populus alba, Cytisus scoparius, Paulownia tomentosa ) and naturally growing vegetation was carried out at a real-scale in order to phytoremediate and functionally recover a soil contaminated by metals (Zn, Pb, Cd, Ni, Cu, Cr), hydrocarbons (TPH) and polychlorobiphenyls (PCB). All the plants were effective in two years in the reclamation of the polluted soil, showing an average reduction of about 35%, 40%, and 70% in metals, TPH and PCB content, respectively. As regards the plants, the poplar contributed the most to organic removal. In fact, its ability to take up and detoxify organic pollutants is well known. Paulownia tomentosa, instead, showed high metal removal. The Cytisus scoparius was the least effective plant in soil decontamination. The recovery of soil functionality was followed by enzyme activities, expressing the biochemical processes underway, and nutrient content useful for plant growth and development. Throughout the area, an enhancement of metabolic processes and soil chemical quality was observed. All the enzymatic activities showed a general increase over time (until 3-4 fold than the initial value for urease and β-glucosidase). Moreover, Cytisus scoparius, even though it showed a lower decontamination capability, was the most effective in soil metabolic stimulation.